Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.5194/bg-3-515-2006
|View full text |Cite
|
Sign up to set email alerts
|

Warming mineralises young and old soil carbon equally

Abstract: Abstract. The temperature sensitivity of soil organic carbon decomposition is critical for predicting future climate change because soils store 2-3 times the amount of atmospheric carbon. Of particular controversy is the question, whether temperature sensitivity differs between young or labile and old or more stable carbon pools. Ambiguities in experimental methodology have so far limited corroboration of any particular hypothesis. Here, we show in a clear-cut approach that differences in temperature sensitivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 28 publications
(41 reference statements)
4
71
1
1
Order By: Relevance
“…Some have found that the more labile SOM is more temperature sensitive (Liski et al, 1999;Giardina and Ryan, 2000), while others have found that the less labile SOM is more temperature sensitive (Bosatta and Ågren, 1999;Bol et al, 2003;Knorr et al, 2005;Fierer et al, 2005). Still other studies have found results indicating diff erent SOM fractions have the same temperature sensitivity (Fang et al, 2005;Conen et al, 2006).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Some have found that the more labile SOM is more temperature sensitive (Liski et al, 1999;Giardina and Ryan, 2000), while others have found that the less labile SOM is more temperature sensitive (Bosatta and Ågren, 1999;Bol et al, 2003;Knorr et al, 2005;Fierer et al, 2005). Still other studies have found results indicating diff erent SOM fractions have the same temperature sensitivity (Fang et al, 2005;Conen et al, 2006).…”
mentioning
confidence: 81%
“…Apparent temperature responses can vary substantially when diff erent methods are used to assess temperature sensitivity and similar methods have found varying results between diff erent soils (e.g., Conen et al, 2006 andVanhala et al, 2007). Even aft er accounting for other factors ameliorating temperature controls on decomposition, such as substrate availability, soil moisture, and soil texture, there is signifi cant variation in decomposition responses to diff erences in temperature (e.g., Fissore et al, 2009;Gillabel et al, 2010).…”
mentioning
confidence: 99%
“…However, the evidence for the temperature sensitivity of organic matter decomposition correlated with biochemical recalcitrance is organic matter specific. For example, some studies were able to detect different Q 10 s for different substrates (Knorr et al 2005;Leifeld and Fuhrer 2005;Fierer et al 2006), whereas others were not able to do so or obtained inconsistent results (Fang et al 2005;Reichstein et al 2005b;Conen et al 2006). Conant et al (2011) recently suggested that the physico-chemical protection from decomposition of organic matter (OM) would affect the temperature response of SOM.…”
Section: Effect Of Grazing On Long-term Q 10mentioning
confidence: 99%
“…Recently, extensive debates have been done on temperature sensitivity focusing on the soil organic carbon quality, in which the temperature sensitivity of recalcitrant organic carbon was greater than (Conant et al, 2008a, b;Craine et al, 2010), equivalent to (Fang et al, 2005;Conen et al, 2006), or less than (Liski et al, 1999;Rey and Jarvis, 2006) that of labile organic carbon. However, most of the conclusions were drawn from soil incubation experiments from well-drained upland ecosystems and with less attention to wetland soils (Davidson and Janssens, 2006).…”
Section: Temperature Sensitivity and Its Variationmentioning
confidence: 99%